Design for the well-being of domestic animals: implementation of a three-stage user research model - Kaygan, Pınar; Yargın, Gülşen Töre (Design and Technology Education: An International Journal, 2019)
This paper presents how we, as design educators, integrated user-centeredness into a design studio course project that is concerned with improving well-being of domestic cats and dogs. Since the primary users of the project were identified as domestic animals, we carried out the project in collaboration with experts from a veterinary medicine school who study animal behavior. We developed a three-stage user research model to enable students to familiarize themselves with the physical and emotional needs of the animals at the beginning, and test their prototypes with the users in both the lab and home contexts during the project. The empirical basis of the paper comes from the interviews we conducted with 12 students who participated in the project, in order to explore their experiences of designing for animals. The paper shows that including animals in a design process as participants, through iterative trials in the real use context, serves as a good strategy to not only overcome the challenges of designing for animals, but also teach students the importance of user-centeredness and building empathy in design in a broader sense.